Outpatient Cervical Ripening with Balloon Catheters: A Systematic Review and Meta-analysis. Issue 2 (February 2022) - Pierce-Williams, Rebecca; Lesser, Henry; Saccone, Gabriele; Harper, Lorie; Chen, Vicky; Sciscione, Anthony; Kuper, Spencer; Subramaniam, Akila; Ehsanipoor, Robert; Berghella, Vincenzo
Abstract : OBJECTIVE: To evaluate whether outpatient cervical ripening with a balloon catheter results in a shorter amount of time in the labor and delivery unit when compared with use in the inpatient setting. DATA SOURCES: PubMed, Scopus, Cochrane Library, and ClinicalTrials.gov were searched from their inception until December 2020. No restrictions for language or geographic location were applied. METHODS OF STUDY SELECTION: Using a predefined protocol and search strategy, 1, 152 titles were identified and screened. Randomized controlled trials that compared outpatient and inpatient cervical ripening with balloon catheters were included. TABULATION, INTEGRATION, AND RESULTS: Data extraction and risk of bias assessments were performed by two reviewers. Meta-analysis was performed to produce mean difference for continuous data and risk ratio (RR) for dichotomous data, both with a 95% CI. The primary outcome was the amount of time from admission to the labor ward until delivery. Additional secondary maternal and neonatal outcomes were evaluated. Eight trials (740 patients) were included; six studies (571 patients) reported on our primary outcome. Compared with the inpatient group, outpatient balloon cervical ripening was associated with significantly less time in the labor and delivery unit (outpatient 16.3±9.7 hours vs inpatient 23.8±14.0 hours; mean difference −7.24 hours, 95% CI −11.03 to −3.34). There were no differences in total induction time or total hospital admission. The outpatient group was significantly less likely than the inpatient group to undergo cesarean delivery (21% vs 27%), RR 0.76 (95% CI 0.59–0.98). There were no differences in other maternal or neonatal outcomes. There were no deliveries outside of the hospital and no stillbirths. CONCLUSION: Outpatient balloon cervical ripening in low-risk patients is associated with a decreased amount of time from admission to labor and delivery until delivery. Outpatient balloon cervical ripening is a safe alternative for low-risk patients and has the potential for significant benefits to patients, and labor and delivery units. SYSTEMATIC REVIEW REGISTRATION: PROSPERO, CRD42019140503. Abstract : Outpatient balloon cervical ripening is associated with decreased time in the labor and delivery unit compared with inpatient ripening.